Society, science, and technology: Mariano de Rivero, mining and the birth of Peru as a Republic, 1820-1850 - Deustua, José (2017)
This article studies the relationships between society, science, and technology through an analysis of the personal life of the Peruvian scientist Mariano Eduardo de Rivero y Ustáriz. Starting with his education at the Seminario de San Jerónimo in Arequipa, the Highgate School in London, and the École Royale des Mines in Paris, this study focuses on Rivero’s activities related to mining in Peru and its vicissitudes, from the development of Simon Bolivar’s strategy for the country after Independence had been achieved, through to the uncertainties of the subsequent period of caudillaje. Particular attention is given to capital investments, especially foreign and British, and the technology employed in the mining sector (especially in Cerro de Pasco) in this early Republican period.